Corrosion barrier properties of PMMA-silica coatings for protection of reinforcing steel - Uvida, Mayara C. [UNESP]; Trentin, Andressa [UNESP]; Harb, Samarah V.; Santilli, Celso V. [UNESP]; Hammer, Peter [UNESP] (My University, 2021)
Corrosion of steel metal structures is the principal cause of failure of reinforced concrete and the absence of preventive maintenance results in financial, social, and environmental implications. To overcome this problem, research efforts are directed toward eco-friendly coatings based on organic-inorganic hybrids developed for effective protection of metal surfaces. PMMA (methyl polymethacrylate)-silica were prepared by polymerization of methyl methacrylate (MMA) and 3-(Trimethoxysilyl) propyl methacrylate (MPTS), using the thermal initiator benzoyl peroxide (BPO) and the sol-gel hydrolytic condensation of tetraethoxysilane (TEOS) and MPTS. Several micrometer thick coatings were deposited on carbon steel by dip-coating. The results of the structural analysis performed by infrared spectroscopy confirmed the formation of PMMA-silica hybrid. The electrochemical impedance spectroscopy measurements in 0.6 mol L-1 NaCl solution showed excellent corrosion resistance of up to 100 GΩ cm2 (low-frequency impedance modulus), with a durability of more than 250 days, while similar corrosion resistance but somewhat lower lifetime was obtained in simulated carbonated and alkaline concrete pore solution.
Keywords: Anticorrosion coating; Organic-inorganic hybrid; Reinforcing steel; Sol-gel process